2016
DOI: 10.2147/copd.s100401
|View full text |Cite
|
Sign up to set email alerts
|

COPD exacerbation care bundle improves standard of care, length of stay, and readmission rates

Abstract: IntroductionCOPD is the third leading cause of death in the world. Utilizing care bundles during acute COPD exacerbations results in fewer complications and lower costs. Our aim was to construct a COPD exacerbation care bundle and evaluate the effects on patient care.MethodsWe conducted a prospective analysis of 44 patients admitted with a COPD exacerbation to a single tertiary care facility. Primary outcomes included length of stay, readmission rates, and hospital costs. Secondary outcomes included patient ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 37 publications
0
24
2
1
Order By: Relevance
“…A postdischarge care bundle plan applied to a cohort of 44 COPD patients found the intervention group to have a 30-day readmission rate of 9.1% compared to 54.5% in the control group. 32 Two other studies also demonstrated a decrease in 30-day readmissions when utilizing care bundles, 14.7% from 22.7% 33 and 15.4% from 17.4%. 34 However, not all interventions work.…”
Section: Discussionmentioning
confidence: 87%
“…A postdischarge care bundle plan applied to a cohort of 44 COPD patients found the intervention group to have a 30-day readmission rate of 9.1% compared to 54.5% in the control group. 32 Two other studies also demonstrated a decrease in 30-day readmissions when utilizing care bundles, 14.7% from 22.7% 33 and 15.4% from 17.4%. 34 However, not all interventions work.…”
Section: Discussionmentioning
confidence: 87%
“… 13 – 15 Two recent studies also showed a reduction in LOS with implementation of EHS-based COPD order sets. 13 , 30 These interventions mainly focused on improving adherence to the multidisciplinary components of the order set to reduce LOS and avoid prescription errors rather than promoting a tailored corticosteroid regimen. However, our focus was to educate providers and reduce the corticosteroid dosing by encouraging the use of PowerPlan.…”
Section: Discussionmentioning
confidence: 99%
“…These conditions present acute events leading to worsening of symptoms beyond the usual daily variations and are a major cause of morbidity and mortality (4). They accelerate the decline in lung function and thus promote the frequent use of medications, visits to the clinics and greater health care costs (5)(6)(7). The significant health and economic consequences of COPD exacerbation are still challenging for health care systems worldwide.…”
Section: Introductionmentioning
confidence: 99%